Effectiveness of diabetes in pregnancy study group India diagnostic criterion in detecting gestational diabetes mellitus: a rural Bangalore study - Saxena, Rajiv Kumar; Ansari, Noor Fathima Tameem; Singh, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The oral glucose tolerance test (OGTT) is considered the current standard for diagnosis of gestational diabetes mellitus (GDM). International association of diabetes and pregnancy study groups (IADPSG) recommends OGTT, with fasting, one-hour and two-hour venous blood samples drawn after intake of 75g oral glucose. In the Indian context, diabetes in pregnancy study group in India (DIPSI) recommends glucose challenge test (GCT), where 75 g glucose is given irrespective of the fasting state, and a single venous sample is drawn after two-hour. Diagnosis of GDM is made, if any cut-off value is met or exceeded. This prospective study was conducted to compare the DIPSI and IADPSG criteria for diagnosis of GDM. Methods: Pregnant women between 24 to 28 weeks of gestation were subjected to non-fasting GCT. Capillary sample were also drawn simultaneously using Accu check active glucometer. These women were counselled to undergo a standard 75gram OGTT, within a week of recruitment. Results: According to IADPSG criteria, 17.6% (18/102) of our participants had GDM, as compared to 19.6% (20/102) by DIPSI criteria using venous samples, and 25.3% (25/99) by capillary sample method. Sensitivity and specificity of GCT using venous sample was 72.22% and 91.67%, and using capillary sample was 70.59% and 84.15% respectively. DIPSI criteria using venous samples wrongly labelled 8.3% women as GDM, and capillary samples wrongly labelled 15.9% women as GDM. More importantly DIPSI criteria using venous samples labelled 27.8% women as false-negative and capillary samples labelled 29.4% women as false-negative for GDM. Almost one quarter of women with GDM will be missed if DIPSI criteria is used as a universal screening modality. Conclusions: We suggest that the IADPSG criteria be used for diagnosis of GDM in antenatal women in India.